Quality of young labor in ethnic minority groups - Case study of Quan Hoa district, Thanh Hoa province - Truong, Cong Diep (2017)
The research í to explore the important factors that influence quality of young labor in ethnic minorrity groups from the case study of Quan Hoa, Thanh Hoa province. Particularly, it is to examine the role of vocationnal training on improving quality of young labor in ethnic minority groups.